STUDY OF UNMANNED AIR VEHICLES UNDER EXTERNAL IMPACT: STUDY OF UNMANNED AIR VEHICLES UNDER EXTERNAL IMPACT - Getsov, Petar; Jordanov, Dimitar; Bo, Wang (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
By modeling a unmanned air vehicles, the possibilities for impact on the operation of the autopilot for the purpose of terminating the flight and destroying the aircraft were examined.